The mindful librarian : connecting the practice of mindfulness to librarianship - Moniz, Richard; Eshleman, Joe; Henry, Jo; Slutzky, Howard; Moniz, Lisa (Chandos information professional series., 2016)
A series of essays which examine how mindfulness, while helpful in its own right, can be specifically applied to library services of all kinds and at all levels. By dealing proactively with changes, staff can provide tools for better focus, greater resiliency, and reduced stress.